On a High Order Spin Wave System with a Nonlinear Free Term (Journal of Partial Differential Equations, 2006)
In this paper, we deduct a new spin wave model in lattices, which is a nonlinear high order degenerate parabolic system with a nonlinear free term. In a further theoretical study, by using a parameter ∈ approximation, the existence of a weak solution has been obtained.
Keywords: Spin wave; high order system; degenerate parabolic equations; existence of solution